ANALISIS PENGGUNAAN MODAL KERJA DENGAN METODE RENTABILITAS PADA CV. MULYA KARYA PADA PROYEK DENGAN SISTEM PEMBAYARAN TERMIN DAN TURN KEY - Dharma Warsika, Putu (Jurnal Ilmiah Teknik Sipil; Vol. 16, No. 1 Januari 2012, 2012)
A company engaged in the service sector has a purpose, namely to get the maximum benefit for survival. To achieve these objectives, the company will rely heavily on the management in regulating the activities of firms, especially in terms of financial function which includes all activities associated with business firms to obtain resources and allocate those funds accordingly. Planning and working capital arrangement are intended to gain efficient benefit for company, because the company's working capital management efficiency becomes very important for the growing and sustainability of the company. This requires a project management to have a good knowledge of working capital so that later can analyze the use of working capital to generate profits by using a specific method (measuring instrument). Profitability is a method that can be used by management/ owners of the contractor to determine the efficiency of working capital in a project to create profits. The analysis result showed that the operating margin for the term of payment systems on Banyubiru project in 2006 was the highest percentage of 60.10% compared to the project in 2005 (59.92%) and in 2007 (60.01%). This means that the turnover of working capital used in the project in 2006 Banyubiru is faster than the project in 2005 and 2007.
Keywords: Profitability, Efficiency, Operating Margin